Graham/Hijmans/Kamp/Watkins Family Reunion at Lake Nacimiento - Watkins, Howard::::::::: (1989)
Enjoying the EZ-UP shade; Gail Graham (long red hair) and Frances Kamp (white hair on left; Robin Watkins, Carey Hijmans and Jackie Hijmans on right